Evaluation of the Digital Ventilated Cage® system for circadian phenotyping - Selma Tir; Russell G. Foster; Stuart N. Peirson (Scientific Reports)
Abstract The study of circadian rhythms has been critically dependent upon analysing mouse home cage activity, typically employing wheel running activity under different lighting conditions. Here we assess a novel method, the Digital Ventilated Cage (DVC®, Tecniplast SpA, Italy), for circadian phenotyping. Based upon capacitive sensors mounted under black individually ventilated cages with inbuilt LED lighting, each cage becomes an independent light-controlled chamber. Home cage activity in C57BL/6J mice was recorded under a range of lighting conditions, along with circadian clock-deficient cryptochrome-deficient mice (Cry1 −/− , Cry2 −/− double knockout). C57BL/6J mice exhibited a 24 h period under light/dark conditions, with a free-running period of 23.5 h under constant dark, and period lengthening under constant light. Animals displayed expected phase shifting responses to jet-lag and nocturnal light pulses. Sex differences in circadian parameters and phase shifting responses were also observed. Cryptochrome-deficient mice showed subtle changes in activity under light/dark conditions and were arrhythmic under constant dark, as expected. Our results show the suitability of the DVC system for circadian behavioural screens, accurately detecting circadian period, circadian disruption, phase shifts and mice with clock defects. We provide an evaluation of the strengths and limitations of this method, highlighting how the use of the DVC for studying circadian rhythms depends upon the research requirements of the end user.